Keratin cyst as a diagnostic pitfall in aspiration cytology of phyllodes tumor. Issue 10 (15th July 2021) - Paul, Pranoy; Agrawal, Shruti; Kumar, Kranthi; Chaudhary, Mriganki; Rao, Shalinee; Ravi, Bina
Abstract: Background: Phyllodes tumor (PT) is a fibroepithelial lesion of breast known for presence of a heterogenous stroma. However occurrence of a keratin cyst within PT is a rare incidence. An inadequate sampling during fine needle aspiration (FNA) of such lesions may result in an erroneous cytological diagnosis. Case report: In the present case, ultrasound guided FNA smears from the breast lump in a 31‐year‐old lady with a clinical suspicion of malignancy, were repeatedly interpreted as an epidermal inclusion cyst, which was ultimately reported as a borderline PT on mastectomy. Conclusion: The case report aims at highlighting the importance of a diligent FNA technique keeping in mind the possibility of the various uncommon lesions especially while dealing with such a heterogenous tumor as phyllodes.